Integration of Transformational Skills and Digital Literacy in AI-Driven Hybrid Learning - Mega Rifatul Amalia; Dewi Cahyani (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze the integration of transformational skills and digital literacy as a strategy for developing human resources (HR) among university students in the era of Artificial Intelligence (AI) and hybrid learning. The research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation involving lecturers, students, and university management. The results show that transformational skills play a role in shaping students’ character to be independent, adaptive, and visionary, while digital literacy enhances technological competence to support the learning process and readiness for a technology-based workforce. Although digital facilities on campus are adequate, their utilization remains suboptimal due to limitations in devices, internet access, and training. The integration of these two aspects serves as a strategic step in creating excellent, creative, and globally competitive students. Educational institutions play a crucial role through the strengthening of digital curriculum policies, the provision of cyber laboratories, and technology training. Thus, the synergy between transformational skills and digital literacy becomes the main foundation in shaping adaptive and competitive student human resources in the era of artificial intelligence. Keywords : Transformational Skills, Digital Literacy, Student Human Resource Development.